Oligotrophic lagoons of the South Pacific Ocean are home to a surprising number of novel eukaryotic microorganisms. (28th September 2016) - Kim, Eunsoo; Sprung, Ben; Duhamel, Solange; Filardi, Christopher; Kyoon Shin, Mann
Summary: The diversity of microbial eukaryotes was surveyed by environmental sequencing from tropical lagoon sites of the South Pacific, collected through the American Museum of Natural History (AMNH)'s Explore21 expedition to the Solomon Islands in September 2013. The sampled lagoons presented low nutrient concentrations typical of oligotrophic waters, but contained levels of chlorophyll a, a proxy for phytoplankton biomass, characteristic of meso‐ to eutrophic waters. Two 18S rDNA hypervariable sites, the V4 and V8–V9 regions, were amplified from the total of eight lagoon samples and sequenced on the MiSeq system. After assembly, clustering at 97% similarity, and removal of singletons and chimeras, a total of 2741 (V4) and 2606 (V8–V9) operational taxonomic units (OTUs) were identified. Taxonomic annotation of these reads, including phylogeny, was based on a combination of automated pipeline and manual inspection. About 18.4% (V4) and 13.8% (V8–V9) of the OTUs could not be assigned to any of the known eukaryotic groups. Of these, we focused on OTUs that were not divergent and possessed multiple sources of evidence for their existence. Phylogenetic analyses of these sequences revealed more than ten branches that might represent new deeply‐branching lineages of microbial eukaryotes, currently without any cultured representatives or morphological information.